2018
DOI: 10.5535/arm.2018.42.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Reference Value for Infrapatellar Branch of Saphenous Nerve Conduction Study: Cadaveric and Clinical Study

Abstract: ObjectiveTo determine the optimal stimulation and recording site for infrapatellar branch of saphenous nerve (IPBSN) conduction studies by a cadaveric study, and to confirm that obtained location is practically applicable to healthy adults.MethodsTwelve lower limbs from six cadavers were studied. We defined the optimal stimulation site as the point IPBSN exits the sartorius muscle and the distance or ratio were measured on the X- and Y-axis based on the line connecting the medial and lateral poles of the patel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Kim and Tran et al. [7-8] also conducted cadaver studies to determine the optimal stimulation and recording site for the IPBS nerve and similarly found that there was variability in the location of the branch. Depending on the height of the patient, this line can span many centimeters, and in order to treat the entire line, as seen in Figure 1, eight or more cycles of cryoablation need to be performed.…”
Section: Technical Reportmentioning
confidence: 99%
“…Kim and Tran et al. [7-8] also conducted cadaver studies to determine the optimal stimulation and recording site for the IPBS nerve and similarly found that there was variability in the location of the branch. Depending on the height of the patient, this line can span many centimeters, and in order to treat the entire line, as seen in Figure 1, eight or more cycles of cryoablation need to be performed.…”
Section: Technical Reportmentioning
confidence: 99%